The lived experience of family members of older people who have died by suicide in rural China - Mengyun Chen; Xiubin Zhang; Brendan McCormack (Wiley, 2023)
Abstract Aim The aim of the study is to provide insight and facilitate a deeper understanding of family members who have experienced their older family member's suicide. Design Interpretative phenomenological analysis (IPA) study. Methods Semi‐structured individual interviews with five family members of older people who died by suicide recruited from a rural area of Shanxi Province, China. Smith's (2009) six steps of IPA was used for data analysis. Results Three main themes emerged from the study: (a) Initial psychological reactions; (b) Long‐term life effects; (c) Social attitudes. The study shows how the family members of older people who died by suicide have experienced stigmatization and felt largely ignored. A suicide event poses a challenge to the future living quality of the family members. The study also highlights that it is necessary to pay attention to families of older people who died by suicide and providing support is required to improve the quality of life of these family members in rural China. Conclusion The study adds to the understanding of the lived experience of family members of older people who died by suicide in less economically developed rural areas. Patient or Public Contribution Patients and the public were not involved in the design, conduct or reporting of this study. Participants of this study helped with recruitment via snowball sampling.